Estabilidad del color de resinas compuestas nanohíbridas sometidas a diferentes sistemas de pulido sumergidos en una solución pigmentadora - Chamba Herrera, Marlon Ulises (2018)
The objective of the present study consisted in analyzing the chromatic changes in filling resins Nanohybrids Opallis and Filtek Z350 XT by using two polishing systems; conventional polishing system and conventional polishing system plus resealing after being immersed in coffee for 30 days, evaluating the color stability and efficiency of conventional polishing system and conventional polishing system plus resealing. The study was of type experimental in vitro, in which a total of 62 Filtek Z350 XT and Opallis A2 enamel composite resin samples were used, divided into 2 groups, being thirty for each trademark of resin. Each group was divided into 2 subgroups according to the polishing system, subgroup 1, conventional polishing system and subgroup 2, conventional polishing system plus resealing and in each subgroup we worked with 15 samples, which were 10 mm in diameter and 2 mm in height, these were submerged in coffee for a period of 30 days. A sample was used as a control group for each resin. The reading of the color was performed with the VitaEasyshade spectrophotometer before and after each experimental time. The conventional polishing system plus resealing presented greater stability of color and efficiency against the conventional polishing system in the samples of the composite resin Filtek Z350 XT and Opallis. Color stability in Filtek Z350 XT resin using as a pigmenting agent to the coffee had a significant difference between the conventional polishing system and the conventional polishing system plus resealing, this being this the one that less changes presented. Keywords: Color, Chromatic Stability, Composite Resin, Coffee, Pigmentation, Dental Polishing, Spectrophotometry.